RELIGIOUS COUNSELING GUIDANCE FOR YOUTH MENTAL HEALTH - Fatimah; Andriyani; Masyitoh; Ai-Ainun Astuti, Devi Yulia; Danang Onggo Wasito; Reza Nuur Wahyuningtias (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
To maintain the mental health of adolescents, one of the factors that can improve the mental health of adolescents is religious education. Adolescence is an unstable period where teenagers often fall or go in the wrong direction, so they need guidance from various parties/means. The role of Religion is crucial because the teachings are very straight and are shunned by inappropriate thoughts. This study uses a literature review method where the researcher conducts a series of studies involving various kinds of information from the library, such as books, encyclopedias, documents, and so on, to find various theories and ideas which can then be formulated according to the research objectives. The results of research from various literature sources indicate that the factor of religious education by carrying out religious activities such as dhikr, reading the Qur'an, praying, and getting closer to Allah SWT will give peace of mind and soul so that it can avoid disease. Mental disorders. Therefore, instill religious teachings as early as possible and get closer to Allah SWT. Religious activities such as dhikr, reading the Qur'an, and prayer can provide peace of mind, mind, and soul to reduce the risk of developing disorders. Mentally.